2019
DOI: 10.3389/fchem.2019.00192
|View full text |Cite
|
Sign up to set email alerts
|

Fluoro-Aryl Substituted α,β2,3-Peptides in the Development of Foldameric Antiparallel β-Sheets: A Conformational Study

Abstract: α,β 2,3 -Disteroisomeric foldamers of general formula Boc( S- Ala-β-2 R ,3 R- Fpg) n OMe or Boc( S- Ala-β-2 S ,3 S- Fpg) n OMe were prepared from both enantiomers of syn H-2-(2-F-Phe)-h-PheGly-OH (named β-Fpg) and S- alanine. Our peptides show two appealing feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 49 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…The main drawback is their lack of proteolytic stability. This issue can be overcome by using peptidomimetics, compounds containing non-natural amino acids or non-peptidic structural elements, capable of mimicking the actions of a natural parent peptide [ 42 , 43 ].…”
Section: Peptides In Electrospinningmentioning
confidence: 99%
See 1 more Smart Citation
“…The main drawback is their lack of proteolytic stability. This issue can be overcome by using peptidomimetics, compounds containing non-natural amino acids or non-peptidic structural elements, capable of mimicking the actions of a natural parent peptide [ 42 , 43 ].…”
Section: Peptides In Electrospinningmentioning
confidence: 99%
“…Indeed, they could be characterized by different secondary structures depending on their amino acid sequences [ 41 ]. The secondary structures determine the 3D folded structures, formed by non-covalent interactions that are at the base of the aggregate formation [ 43 , 44 , 45 ]. In conclusion, very often, peptides with a stable conformation are able to self-assemble, and this is also one of the most important factors for the formation of well-defined electrospun fibers [ 41 ].…”
Section: Peptides In Electrospinningmentioning
confidence: 99%
“…Bucci et al synthesized a Δ 2 -isoxazoline scaffold, fused with a pyrrolidine ring, of general formula 101, able to stabilize a parallel β-hairpin. [65] Compound 101 was synthesized using a diasteroselective [1,3]-cycloaddition reaction between chloroxime 99 and pyrroline derivative 100 (A) in Scheme 22), whose stereochemical outcome is strictly dependent on the base. Computational studies confirmed that π-interactions between the phenyl substituents of the two reagents favor the formation of the 3aR,6aS-isomer 101 b.…”
Section: Bicyclic Compoundsmentioning
confidence: 99%
“…Benzodiazepinones 120 were synthesized from compounds 124 through Boc protecting group removal, followed by imine formation. Pyrrolo [1,2-d] [1,4] benzodiazepinones 121 and 122 were obtained from olefins 124 as starting materials. Their transformation into the corresponding di-carbonyl compounds through oxidation of double bond was first performed, followed by intramolecular reaction of deprotected amino group with the two carbonyl moieties giving pyrrole ring.…”
Section: Policyclic Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation